Uremic pruritus: Still itching - AŞICIOĞLU, EBRU; KOÇ, MEHMET (My University, 2011)
Uremic pruritus is a common complication of chronic renal failure. It affects 50% of patients undergoing hemodialysis or peritoneal dialysis. The causes of pruritus in uremic patients are still unknown. Xerosis, intradermal microprecipitation of divalent ions, secondary hyperparathyroidism, peripheral neuropathy, allergic reactions, hypersensitivity and histamine have been considered as pathogenetic factors. The cornerstone of therapy for uremic pruritus is regular, intensive, efficient dialysis. Other therapeutic measures include topical emollients, topical capsaicin, systemic antihistaminics, gabapentine and phototherapy.
Keywords: Hemodialysis; Itch; Uremia